Designs of duty: Using exhibits to build partnerships. Issue 1 (2nd January 2019) - Hildebrandt, Beth; Knight-Davis, Stacey; Pionke, J. J.; Cougill, Andrew
Abstract: Exhibits in academic libraries are drivers for outreach. Many exhibit programs center on national traveling exhibits often because they are well done and already completed. The only input necessary from a host institution is space and a small amount of time to put up the exhibit. Locally made exhibits create a stronger connection to the community, but they are more expensive in terms of time for research and creating the exhibit, and money for printing. The adage "many hands make light work" accurately describes the local exhibit creation process when multiple groups come together. Partnerships between libraries to share exhibit content broaden the Pool of exhibit possibilities and raise awareness of exhibit programs for all partners. In this case, an exhibit at the University of Illinois at Urbana-Champaign that focused on veterans and their service-related tattoos was picked up and built upon by Eastern Illinois University. This case study covers multiple libraries, both academic and public, sharing an exhibit about veterans and their tattoos, providing outreach opportunities to veteran and service member populations at all participating libraries